The Online Shopping Behavior of Indonesian Generation X - I Made Sindhu Yoga; Ni Putu Silka Triami (Journal of Economics, Business, and Accountancy Ventura, 2020)
E-commerce is one of the information technologies that influence consumer behavior. Generation X is characterized by a higher internet adoption rate than the previous generation. As digital immigrants, this generation behavior toward using e-commerce is an interesting phenomenon to be studied. Thus, this study aims to examine the acceptance and use of e-commerce among Generation X using Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) theory. The research sample was 369 Generation X respondents in Indonesia who used e-commerce and were selected using purposive sampling. The questionnaires were distributed online and then analyzed using structural equation modeling. The findings showed that Generation X acceptance towards e-commerce were influenced by performance expectancy, hedonic motivation, habit, price value, and behavior intention. In contrast, effort expectancy, facilitating condition, and social influences) were not found to be the predictor that influenced Generation X to use e-commerce. This paper offers valuable insights for e-commerce founders in the development and refinement of e-commerce platforms.